Electromagnetic Levitator - Mohamad, Najmiah Radiah; Chau, Man Siang; Ahmad Sadhiqin, Mohd Isira; Adie, Mohd Khafe; Salleh, Azahari; Nur Fatihah, Azmi (2012)
This paper, we design magnetic levitation system that deals with the knowledge of electromagnetism and the control switching application. The concept of this design is to achieve the state of equilibrium where the magnetic attraction counterbalances the force of gravity pulling on an object. The control system in this design is formed by a PIC Microcontroller and several op-amps. Using photo sensors to provide a feedback loop, the control system employs a closed-loop control in controlling the current through the electromagnet.